2021
DOI: 10.1089/elj.2020.0650
|View full text |Cite
|
Sign up to set email alerts
|

Ranked Choice Voting in Maine from the Perspective of Local Election Officials

Abstract: In 2018, Maine became the first American state to use ranked choice voting in statewide and congressional elections. In a decentralized system of election administration local officials play an important role implementing new voting rules. We examine the implementation of ranked choice voting based on a survey of municipal clerks and interviews with several election officials in Maine. We test hypotheses derived from policy implementation theory in assessing election officials' evaluations of ranked choice vot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Since the year 2000, certain jurisdictions have taken this route, including Henderson in North Carolina, Memphis in Tennessee, Pierce County in Washington, Aspen in Colorado, and temporarily in Burlington, Vermont, as well as on a statewide basis in Maine. A survey of municiple clerks in Maine found that most did not want to continue with RCV (Anthony et al, 2021). A number of these locales have repealed their RCV systems shortly after their implementation due to various concerns related to fairness - though Maine has since reinstated RCV for some elections and is considering an expansion of RCV for more positions (Whittle, 2023).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Since the year 2000, certain jurisdictions have taken this route, including Henderson in North Carolina, Memphis in Tennessee, Pierce County in Washington, Aspen in Colorado, and temporarily in Burlington, Vermont, as well as on a statewide basis in Maine. A survey of municiple clerks in Maine found that most did not want to continue with RCV (Anthony et al, 2021). A number of these locales have repealed their RCV systems shortly after their implementation due to various concerns related to fairness - though Maine has since reinstated RCV for some elections and is considering an expansion of RCV for more positions (Whittle, 2023).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In the 2018 race for Maine’s second congressional seat, the Democratic candidate Jared Golden and two independent candidates publicly asked for their voters to rank the other two candidates as their second and third choices. Republican incumbent Poliquin, by contrast, did not (Anthony et al, 2021). Research finds that voters in the race were influenced by these endorsements, with at least two-thirds of supporters of the three other candidates ranking additional preferences while Poliquin supporters were much less likely to (Alvarez-Rivera, 2018; Reilly, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in a survey among registered voters in Cary, North Carolina, approximately 1 year after its first RCV election, 41% of respondents reported a low level of understanding of the rule (Town of Cary, 2016). More than two thirds of Maine's municipal clerks believed that voters did not understand RCV (Anthony et al, 2019, p. 18).…”
Section: Previous Research About Rcv and Runoff Relevant To The Impac...mentioning
confidence: 99%